Effects of simvastatin on pulmonary fibrosis, pulmonary hypertension and exercise capacity in bleomycin‐treated rats. (25th March 2013) - Schroll, S.; Lange, T. J.; Arzt, M.; Sebah, D.; Nowrotek, A.; Lehmann, H.; Wensel, R.; Pfeifer, M.; Blumberg, F. C.
Abstract Aim Pulmonary fibrosis is often complicated by pulmonary hypertension. Statins reduce fibroblast activity in vitro and pulmonary hypertension in vivo. We investigated whether Simvastatin exerts beneficial effects on pulmonary fibrosis and pulmonary hypertension in Bleomycin‐treated rats in vivo. Methods Rats were randomly assigned to controls, Bleomycin, Bleomycin plus Simvastatin from day 1 to 28 and Bleomycin plus Simvastatin from day 13 to 28. 28 days after Bleomycin instillation, right ventricular systolic pressure (RVSP), right ventricular mass (RV/(LV+S)), right ventricular and circulating brain natriuretic peptide (BNP) levels were determined to assess pulmonary hypertension. Pulmonary hydroxyproline content (HPC), pulmonary connective tissue growth factor (CTGF) transcription and lung compliance (LC) were analysed to characterize pulmonary fibrosis. Exercise capacity was determined by treadmill tests. Results Compared with controls, Bleomycin increased RVSP, RV/(LV+S), BNP levels, HPC and CTGF transcription and decreased LC significantly. Simvastatin administered from day 1 to 28 normalized all these parameters. Simvastatin administered from day 13 to 28 had no effect on HPC and LC, but reduced RV/(LV+S) significantly and induced a strong trend to lower RVSP and BNP levels. Exercise capacity was reduced by Bleomycin. Simvastatin significantly improved exercise intolerance in both treatment groups. Conclusions Simvastatin prevents the development of pulmonary fibrosis, but fails to attenuate already established pulmonary fibrosis. In contrast, it ameliorates pulmonary hypertension and thereby exercise capacity in the prevention and the treatment group regardless of its effects on pulmonary fibrosis. Whether statins are a treatment option in humans with pulmonary fibrosis needs to be investigated by further study.